Social isolation, mental health, and use of digital interventions in youth during the COVID-19 pandemic: A nationally representative survey. Issue 1 (9th March 2021) - Rauschenberg, Christian; Schick, Anita; Goetzl, Christian; Roehr, Susanne; Riedel-Heller, Steffi G.; Koppe, Georgia; Durstewitz, Daniel; Krumm, Silvia; Reininghaus, Ulrich
Abstract: Background: Public health measures to curb SARS-CoV-2 transmission rates may have negative psychosocial consequences in youth. Digital interventions may help to mitigate these effects. We investigated the associations between social isolation, COVID-19-related cognitive preoccupation, worries, and anxiety, objective social risk indicators, and psychological distress, as well as use of, and attitude toward, mobile health (mHealth) interventions in youth. Methods: Data were collected as part of the "Mental Health And Innovation During COVID-19 Survey"—a cross-sectional panel study including a representative sample of individuals aged 16–25 years ( N = 666; Mage = 21.3; assessment period: May 5, 2020 to May 16, 2020). Results: Overall, 38% of youth met criteria for moderate or severe psychological distress. Social isolation worries and anxiety, and objective risk indicators were associated with psychological distress, with evidence of dose–response relationships for some of these associations. For instance, psychological distress was progressively more likely to occur as levels of social isolation increased (reporting "never" as reference group: "occasionally": adjusted odds ratio [aOR] 9.1, 95% confidence interval [CI] 4.3–19.1, p < 0.001; "often": aOR 22.2, CI 9.8–50.2, p < 0.001; "very often": aOR 42.3, CI 14.1–126.8, p < 0.001). There was evidence that psychological distress, worries, and anxiety were associated with a positive attitude toward using mHealth interventions, whereas psychological distress, worries, and anxiety were associated with actual use. Conclusions: Public health measures during pandemics may be associated with poor mental health outcomes in youth. Evidence-based digital interventions may help mitigate the negative psychosocial impact without risk of viral infection given there is an objective need and subjective demand.